Brief Report: Patients' Experiences and Opinions After Desimplification of Their Single-Tablet Regimens for the Treatment of HIV Infection: A Survey in a Multicentre Cohort. (1st May 2022) - Suárez-García, Inés; Ruiz-Algueró, Marta; Alejos, Belén; García-Yubero, Cristina; Belza, Mª José; Espacio, Ramón; Hernández, Juanse; Muñoz Sánchez, Josefa; Garaialde, Ainhoa; Alonso Socas, María del Mar; Alcaraz, Antonia; Pierola Ruiz de Galarreta, Beatriz; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: The aims of this study were to describe patients' experiences after single-tablet regimen (STR) desimplification and its impact on self-reported treatment adherence and quality of life. Methods: We performed a survey among all patients from the multicenter cohort of the Spanish HIV/AIDS Network who had desimplified the STRs dolutegravir/abacavir/lamivudine (DGT/ABC/3TC) or rilpivirine/tenofovir disoproxil fumarate/emtricitabine to their separate components (DTG + generic ABC/3TC or RPV + generic TDF/FTC) between December 2016 and November 2018. Results: Among 216 patients who fulfilled inclusion criteria, 138 (63.9%) completed the questionnaire. Most of the patients (78.3%) knew what generic drugs are, only 8.7% believed that treatment with 2 pills is less effective than treatment with an STR, and 67.4% agreed that it is reasonable to take 2 pills instead of 1 for HIV treatment to decrease costs for the health care system. After desimplification, 13.0% of the patients stated they had more secondary effects, 8.0% had forgotten one or more doses more frequently than before, and 10.9% had sometimes forgotten to take 1 pill, but not the other. A proportion of 30.4% reported not being happy to take more pills a day, and 10.1% experienced a worse quality of life after the treatment desimplification. Conclusions: After STR desimplification, most of the patients had a fair knowledge about generic antiretrovirals, and they agreed to desimplify their STR to decrease costs. Although almost a third of the respondents were not happy to take 2 pills a day, only a minority reported worse adherence or quality of life.